AVAILABILITY OF ROOM FACILITIES ON GUEST SATISFACTION STAYING AT KHAS PARAPAT HOTEL - Robert Deffie (Akademi Pariwisata Darma Agung, 2023)
Hotels that are part of the tourism industry that are directly involved with tourists or guests staying overnight who need to improve themselves in providing hotel facilities, including food and drinks, and other services. One of the hotel facilities is room facilities that are intended for tourists or guests who are staying overnight. Tourists or guests who stay overnight will get satisfaction if they get the available guest room facilities that are complete and according to their wishes, on the other hand tourists or guests who stay overnight will get dissatisfaction or disappointment if they get the available guest room facilities that are incomplete and not suitable.Tourists or guests who stay overnight will get satisfaction if the available guest room facilities are complete and according to their wishes, whereas tourists or guests who stay overnight will get dissatisfaction or disappointment if the available guest room facilities are incomplete and not suitable. This study aims to find out how the Availability of Room Facilities Against Guest Satisfaction Staying at the Hotel Khas Parapat is based on bedroom facilities, bathroom facilities, guest supplies in the bedroom, and guest supplies in the bathroom. This type of research is based on descriptive qualitative research with a sample of 68 overnight guests. This study resulted that the availability of room facilities on guest satisfaction from the stay of 35 people (52%) stated that it was quite suitable for Hotel Khas Parapat